2018
DOI: 10.1002/hyp.13280
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic response of run‐off to forest disturbance in small mountain catchments

Abstract: Stable water isotopes were applied to trace hydrological processes in an undisturbed (mature spruce forest) and a nearby disturbed (deforested from a bark beetle outbreak) lake catchments in the Czech Republic. Both catchments are situated above 1,000 m a.s.l. within the Šumava National Park and have similar environmental conditions. The isotopic compositions of precipitation, creeks, springs, and lakes were sampled at 3-week intervals over one hydrological year. Water inputs to catchments were derived from is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…When the SLP difference is weak (negative NAO mode), the North Atlantic jet is weakened and shifted to the south, bringing less heat, allowing an excess of Siberian cold air intrusions to the European continent, and bringing more moisture to southern Europe and its surroundings [99], including practically the entire study area. Besides the primary marine sources, recycled moisture from the Eurasian landmass at the eastern part of the region also becomes significant driver in continental areas [37,100,101]. Further, given the moisture transport trajectories from the ocean, weather systems travel a greater distance over land and are therefore affected by the processes of rainout, re-evaporation and moisture mixing in a positive NAO-mode.…”
Section: Environmental Controls On Speleothem δ 18 Omentioning
confidence: 99%
“…When the SLP difference is weak (negative NAO mode), the North Atlantic jet is weakened and shifted to the south, bringing less heat, allowing an excess of Siberian cold air intrusions to the European continent, and bringing more moisture to southern Europe and its surroundings [99], including practically the entire study area. Besides the primary marine sources, recycled moisture from the Eurasian landmass at the eastern part of the region also becomes significant driver in continental areas [37,100,101]. Further, given the moisture transport trajectories from the ocean, weather systems travel a greater distance over land and are therefore affected by the processes of rainout, re-evaporation and moisture mixing in a positive NAO-mode.…”
Section: Environmental Controls On Speleothem δ 18 Omentioning
confidence: 99%
“…An isotope‐enabled water balance approach is an alternative to direct measurements, and enables partitioning the evaporation component of the ET flux at the watershed scale (Gibson et al, 1993; Gonfiantini, 1986; Jasechko et al, 2013; Telmer & Veizer, 2000; Vystavna et al, 2018). This approach is cost‐effective in comparison to direct hydrological measurements and can be applied at a variety of scales, from a small watershed to a subcontinental river basin worldwide (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Climate-driven patterns in the stable isotope distribution of oxygen and hydrogen in regional air masses across Europe are well understood, and these can be locally applied to distinguish between different moisture sources and tracks, to apportion seasonal contributions of various recharge sources to rivers and/or groundwater [16], and to identify and potentially quantify post-precipitation processes (e.g. evaporation) [17], etc. So far, only two studies have demonstrated this approach in Romania [18,19].…”
Section: Introductionmentioning
confidence: 99%